Biocomposites from waste derived biochars: Mechanical, thermal, chemical, and morphological properties. (March 2016) - Das, Oisik; Sarmah, Ajit K.; Bhattacharyya, Debes
Highlights: Waste derived biochars were used to make polymer based biocomposites. Composites were tested for their mechanical, chemical, thermal, fire properties. Poultry litter biochar with high ash had best mechanical properties in composite. Crystal structure of polypropylene was not disrupted by added biochars. Microscopy revealed biochar pore infiltration by polypropylene. Abstract: To identify a route for organic wastes utilisation, biochar made from various feedstocks (landfill pine saw dust, sewage sludge, and poultry litter) and at diverse pyrolysis conditions, were collected. These biochars were used to fabricate wood and polypropylene biocomposites with a loading level of 24 mass%. The composites were tested for their mechanical, chemical, thermal, morphological, and fire properties. The poultry litter biochar biocomposite, with highest ash content, was found to have high values of tensile/flexural strength, tensile/flexural modulus, and impact strength, compared to other composites. In general, addition of all the biochars enhanced the tensile/flexural moduli of the composites. The crystal structure of polypropylene in the composite was intact after the incorporation of all the biochars. The final chemical and crystal structure of the composite were an additive function of the individual components. The biochar particles along with wood acted as nucleating agents for the recrystallization of polypropylene in composite. Each component in the composites was found to decompose individually under thermal regime. The electron microscopy revealed the infiltration of polypropylene into the biochar pores and a general good dispersion in most composites. The poultry litter composite was found to have lower heat release rate under combustion regime.